1986
DOI: 10.1246/cl.1986.823
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mono- And Multilayer Films of Aromatic Polyimides Using Langmuir–blodgett Technique

Abstract: Monolayer film of polyamic acid alkylamine salt at air–water interface was successfully deposited onto appropriate plates. Subsequent treatment of the multilayer film with a mixture of acetic anhydride and pyridine afforded the multilayer film of polyimide. The distance between two layers of the polyimide multilayer film was estimated to be 4 Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(32 citation statements)
references
References 7 publications
1
30
0
1
Order By: Relevance
“…Therefore, the amphiphilic precursor method has traditionally been used to fabricate polyimide LB films [4]. In this method, long alkyl chain polyamic acid salts or esters are deposited onto solid substrates and imidized by thermal treatment [24]. Only a few examples of LB film formation by direct spreading of soluble polyimides onto the air-water interface can be found in the literature [23,[25][26][27].…”
Section: Films Of Pure Polymermentioning
confidence: 99%
“…Therefore, the amphiphilic precursor method has traditionally been used to fabricate polyimide LB films [4]. In this method, long alkyl chain polyamic acid salts or esters are deposited onto solid substrates and imidized by thermal treatment [24]. Only a few examples of LB film formation by direct spreading of soluble polyimides onto the air-water interface can be found in the literature [23,[25][26][27].…”
Section: Films Of Pure Polymermentioning
confidence: 99%
“…PAA LB films were prepared by the method of Kakimoto and co-workers [35,36]. The benzene-DMAc mixed solution (1:1) of PAA salt (PAAS) with N,N -dimethylhexadecylamine was spread onto the air/water interface.…”
Section: Sample Preparationmentioning
confidence: 99%
“…However, in polymeric LB films, in which chromophoric units are chemically linked to the main chains or side chains, the formation of aggregates can be reduced effectively, providing a homogeneous distribution of chromophores in a two-dimensional plane. Kakimoto et al reported a polyimide LB film, made up of layers with a thickness of a few angstroms [35,36]. In addition to the extreme thinness, the chemical structure of polyimide enables one to introduce various kinds of diamines into the main chain, while keeping the thermal, mechanical, and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Freilich 5 that a ''Precursor Method'' reported by Kakimoto and the addition of electron donors to Kapton polyimhis co-workers. 9,10 Because stacked molecular oride films results in an enhancement of photocurganization and small intermolecular distance, rent by as much as five orders of magnitude comleading to high charge mobility, 11 can be obtained pared to the virgin polymer. Therefore, it is reain Langmuir-Blodgett films, 12,13 it is of interest to sonably expected that incorporating of suitable investigate the photoconductive properties of the electron donors, such as carbazole and/or phthapolyimide LB films with various chemical struclocyanine, into the polyimide backbone will lead ture.…”
Section: Introductionmentioning
confidence: 99%